LAPAROSCOPY IN DIAGNOSTICS AND TREATMENT OF ACUTE RECURRENT OMENTITIS IN CHILDREN - A.V. Nekrutov; O.V. Karaseva (Union of pediatricians of Russia, 2009)
The article describes the results of research of the role of gastro colic omentum in developing an intraperitoneal inflammatory focus. Acute recurrent omentitis cases are systematized by degree of tissue inflammatory alterations in gastro colic omentum and the video laparoscopic semiotics of omentitis stages. The authors offer and justify an original differentiated laparoscopic tactics in line with the morphological state of gastro colic omentum's tissue. It shows the impact of various surgical tactics on the quality of post-operation progress.Key words: children, laparoscopy, acute appendicitis, gastrocolic omentum, omentitis.